Prompt Engineering for Conversational AI Systems: A Systematic Review of Techniques and Applications - Panneer Selvam Viswanathan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article comprehensively analyzes prompt engineering techniques in conversational AI systems, focusing on their implementation and impact on large language model (LLM) performance. The article examines the fundamental principles of effective prompt design, including clarity, contextual framing, and instructional phrasing, while exploring advanced techniques such as prompt chaining, few-shot learning, and domain-specific adaptations. The article investigates role-based prompting strategies and parameter optimization methods, addressing critical challenges in bias mitigation and response consistency. The findings demonstrate that well-crafted prompts significantly enhance LLM output quality across various domains, including healthcare, finance, and education. The article also reveals emerging trends in automated prompt generation and multimodal applications, suggesting future directions for prompt engineering development. This article contributes to the growing knowledge in AI interaction optimization and provides practical guidelines for implementing effective prompt engineering strategies in conversational AI systems.